2015
DOI: 10.1534/genetics.114.173070
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Environmental Variance Causes Nonlinear Relationships Between Traits: Application to Birth Weight and Stillbirth of Pigs

Abstract: There is recent evidence from laboratory experiments and analysis of livestock populations that not only the phenotype itself, but also its environmental variance, is under genetic control. Little is known about the relationships between the environmental variance of one trait and mean levels of other traits, however. A genetic covariance between these is expected to lead to nonlinearity between them, for example between birth weight and survival of piglets, where animals of extreme weights have lower survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 53 publications
(82 reference statements)
2
25
1
Order By: Relevance
“…Stabilizing selection on the mean is expected to reduce V E as demonstrated by Mulder et al. (), whereas intense directional selection is expected to increase V E (Hill and Zhang ; Mulder et al. ).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Stabilizing selection on the mean is expected to reduce V E as demonstrated by Mulder et al. (), whereas intense directional selection is expected to increase V E (Hill and Zhang ; Mulder et al. ).…”
mentioning
confidence: 95%
“…As pointed out above, variation in V E can lead to variation in individual fitness and V E could hence be under selection. Stabilizing selection on the mean is expected to reduce V E as demonstrated by Mulder et al (2015), whereas intense directional selection is expected to increase V E (Hill and Zhang 2004;Mulder et al 2007). Under stabilizing selection, Zhang and Hill (2005) showed that small homogeneity costs or large temporal variation in optimal phenotype and strength of stabilizing selection can maintain V E .…”
mentioning
confidence: 99%
“…To date, the few published estimates of additive genetic variance of predictability are restricted to a captive animal breeding environment (Hill & Mulder, ; Mulder et al ., ; Sae‐Lim et al ., ), except for one study (Mulder et al ., ). Mulder et al .…”
Section: Introductionmentioning
confidence: 99%
“…In a bivariate scenario, Mulder et al . () showed that additive genetic variance in predictability of a linearly selected trait could lead to nonlinear responses for correlated traits. The recent development of a theoretical framework (Hill & Mulder, ; Westneat et al ., ) and of suitable statistical methods (Lee & Nelder, ; Cleasby et al ., ; Mulder et al ., ) offer a way to advance our understanding of these issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation